2011
DOI: 10.1007/s00296-011-2018-4
|View full text |Cite
|
Sign up to set email alerts
|

Osteomalacia caused by tumors in facies cranii mimicking rheumatoid arthritis

Abstract: Tumor-induced osteomalacia (TIO) is an extremely rare metabolic bone disease and the occult offending tumor arising in facies cranii is even more uncommon. In this report, we described 2 middle-aged females with TIO caused by the tumor in facies cranii, which had ever been misdiagnosed as rheumatoid arthritis. Case 1 was present with diffuse bone pain and muscle weakness for 4 years, as well as esotropia in the right eye for 1 month. Case 2 was present with progressive bone pain in low back and hip for 2 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Moreover, our data revealed that the definite diagnosis and effective treatment of TIO was significantly delayed for years. Our data are consistent with repeated reports of delays in diagnosis, improper treatment and prolonged morbidity of TIO patients [8][9][10][11][12][13]18]. A typical example is a case report from E. Michael Lewiecki and his colleague, describing an unusual TIO case presented with musculoskeletal symptoms and fragility fractures [13].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Moreover, our data revealed that the definite diagnosis and effective treatment of TIO was significantly delayed for years. Our data are consistent with repeated reports of delays in diagnosis, improper treatment and prolonged morbidity of TIO patients [8][9][10][11][12][13]18]. A typical example is a case report from E. Michael Lewiecki and his colleague, describing an unusual TIO case presented with musculoskeletal symptoms and fragility fractures [13].…”
Section: Discussionsupporting
confidence: 71%
“…Nevertheless, missed diagnoses or even misdiagnoses with subsequently diagnostic and therapeutic delay (ranging from 3-19 years) are commonly seen in reported cases of TIO, accompanied by prolonged morbidity and poor prognosis [8][9][10][11][12][13]. This reflects the relatively poor recognition of the rare disease among physicians.…”
Section: Definition Of Misdiagnosis and Missed Diagnosismentioning
confidence: 99%
“…Here we present a detailed review of published English literature for TIO cases involving head and neck region ( n = 163) (5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, …”
Section: Discussionmentioning
confidence: 99%
“…TIO is usually missed for many years due to the occult nature of the disease, its non-specific presentations, and the serum phosphate level being unchecked in early routine tests [ 2 , 3 ]. In addition, non-specific signs and symptoms mislead physicians into more common diseases, especially rheumatologic ones such as rheumatoid arthritis and seronegative spondyloarthritis [ 3 , 8 ]. In our case, mistakenly attributing the patient’s signs and symptoms to the psoriatic arthritis for a long time had resulted in multiple complications for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The disease usually presents itself with multiple bone fractures, chronic bone pain and muscle weakness. The diagnosis frequently is missed for many years, leading to several complications in patients [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%